2020
DOI: 10.3390/antiox9090797
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols by Generating H2O2, Affect Cell Redox Signaling, Inhibit PTPs and Activate Nrf2 Axis for Adaptation and Cell Surviving: In Vitro, In Vivo and Human Health

Abstract: Human health benefits from different polyphenols molecules consumption in the diet, derived mainly by their common activities in the gastrointestinal tract and at the level of blood micro-capillary. In the stomach, intestine and colon, polyphenols act as reducing agents preventing lipid peroxidation, generation and absorption of AGEs/ALEs (advanced glycation end products/advanced lipid oxidation end products) and postprandial oxidative stress. The low absorption of polyphenols in blood does not support their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 143 publications
4
73
0
2
Order By: Relevance
“…In this sense, H 2 O 2 can have a dual effect by modulating vascular reactivity, and by a vasodilator effect in the sub mucosal arterioles [ 39 ]. Therefore, the effect depends on the vascular bed in which it is acting [ 40 ] and upon the physiological and pathological conditions [ 41 ]. The effect also depends on the concentration; at 10–100 nM, it has beneficial effects on the vascular reactivity; however, at high concentrations of 1 µM it induces vasoconstriction, inflammation, and cell death [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, H 2 O 2 can have a dual effect by modulating vascular reactivity, and by a vasodilator effect in the sub mucosal arterioles [ 39 ]. Therefore, the effect depends on the vascular bed in which it is acting [ 40 ] and upon the physiological and pathological conditions [ 41 ]. The effect also depends on the concentration; at 10–100 nM, it has beneficial effects on the vascular reactivity; however, at high concentrations of 1 µM it induces vasoconstriction, inflammation, and cell death [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the beneficial effect of the polyphenols present in HSL can be due to a lower generation of H 2 O 2 in the arterioles. H 2 O 2 interacts exogenously with endothelial cell, and penetrates through aquaporins inhibiting phosphatases, NADPH oxidases and activating Nrf2 [ 41 ]. However, the increase in the activity of the SOD isoforms could lead to an increase in the endogenous H 2 O 2 in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…ROS levels are regulated by various enzymatic and non-enzymatic mechanisms. The latter involves also low-weight molecules with pronounced redox properties, such as polyphenols, ascorbic acid, tocopherols, and carotenoids [ 2 , 3 ]. While human beings can biosynthesize some low-weight redox-active molecules, such as kynurenines [ 4 ], the majority of the required antioxidants, ascorbic acid or polyphenols amongst others, needs to be taken up from food [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals may also indirectly activate the Nrf2/Keap1 system by increasing the intracellular levels of oxygen radical species or nitric oxide all of which target cysteine residues of Keap 1. Free oxygen radical species including H 2 O 2 may be either generated directly by phenolics extra- or intracellularly, in the presence of Cu(II) or Fe(III) ions [ 55 , 56 , 60 , 93 , 94 ], or may come from mitochondria [ 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Candidate Mechanisms For a Delayed Impact On Metabolic Contrmentioning
confidence: 99%